Pemanfaatan Kawat Bulu menjadi Kerajinan Tangan untuk Meningkatkan Kreativitas Siswa - Hafizah, Hafizah; Rini Simamora, Indah Anda; Rahayu, Indah Dwi; Khairani, Indah; Khairunnisya, Khairunnisya; Gamiarsih, Antika; Sulvianti, Arifah; Sari, Atika Pratama; Amri, Elvianti; Yusri, Hilman; Astuti, Astuti; Noviardila, Iska (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to evaluate the effectiveness of the implementation of a contextual learning-based leadership project through handicraft activities with wire bristles as the main material at UPT SD Negeri 001 Salo. This project is designed to improve students' creativity, fine motor skills, and self-confidence through the Project Based Learning (PjBL) approach. This study uses a qualitative descriptive approach with a case study method, which aims to describe in depth the process and results of implementing the learning leadership project at UPT SD Negeri 001 Salo. The main focus of the study is on the use of wire bristles as a medium in learning Arts and Crafts. The results show that the project not only succeeded in achieving its main objectives, but also increased student participation, strengthened collaboration between teachers, and created a more active and enjoyable learning atmosphere. These findings reinforce the importance of contextual learning activities that directly involve students and provide space for exploration of creativity. Recommendations are directed at developing sustainable projects and increasing resource support and community participation.